2007
DOI: 10.15809/irriga.2007v12n1p38-53
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa E Distribuição De Precipitações Decendiais Para O Estado Do Paraná

Abstract: ESTIMATIVA E DISTRIBUIÇÃO DE PRECIPITAÇÕES DECENDIAIS PARA O ESTADO DO PARANÁ  Silvio César Sampaio; Manoel Moisés Ferreira de Queiroz; Elisandro Pires Frigo; Adair José Longo; Morgana SuszekSetor de Recursos Hídricos e Saneamento Ambiental (RHESA), Universidade Estadual do Oeste do Paraná,  Cascavel, Paraná, ssampaio@unioeste.br  1 RESUMO O objetivo deste trabalho foi estimar a precipitação provável com 75% de probabilidade nos períodos decendiais, a partir de dados diários de precipitação de 22 postos de med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
11

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
1
5
0
11
Order By: Relevance
“…After this assessment, the two best models were used in the determination of the monthly precipitation probabilities for the region with greater than 100, 150, and 200 mm precipitation. These values were chosen with respect to the rainfall characteristics of the climate types found in the state of Paraná, (SAMPAIO et al 2007, KIST & VIRGENS FILHO 2015. All the statistical analyses in our study were performed using the R statistical software (R DEVELOPMENT CORE TEAM 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After this assessment, the two best models were used in the determination of the monthly precipitation probabilities for the region with greater than 100, 150, and 200 mm precipitation. These values were chosen with respect to the rainfall characteristics of the climate types found in the state of Paraná, (SAMPAIO et al 2007, KIST & VIRGENS FILHO 2015. All the statistical analyses in our study were performed using the R statistical software (R DEVELOPMENT CORE TEAM 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This consists of fitting different probability distributions and, consequently, the performance of goodness-of-fit tests to verify which of the models obtained the best fit to the data. In studies on monthly rainfall probability, the gamma and Weibull distributions are most frequently used due to the positive asymmetry characteristic of the curves, which guarantees values that are different to zero (SAMPAIO et al 2007, SILVA et al 2007, SHARMA & SINGH 2010. Other authors also found satisfactory results with incomplete and mixed gamma distributions (MOREIRA et al 2010, DALLACORT et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Moreira et al (2010), relatam que diversos estudos indicam a distribuição gama, como o meio probabilístico mais confiável na determinação de totais mensais de precipitação. Segundo os autores, diversos trabalhos utilizaram a distribuição gama, como por exemplo, Murta et al (2005), Silva et al (2007), Sampaio et al (2007) A distribuição de probabilidade gama incompleta, tem sido considerada o modelo teórico que melhor ajusta os totais de chuvas mensais para períodos menores, sendo, portanto, o mais utilizado (Hargreaves, 1973;Fonseca e Albuquerque, 1978;Arruda e Pinto, 1980;Varejão-Silva et al, 1984).…”
Section: Introductionunclassified
“…O conhecimento da variação da precipitação, tanto no espaço, como no tempo, é importante para estudos hidrológicos e para o planejamento dos recursos hídricos (Bigg, 1991, Sampaio et al, 2007. Por isso, é essencial na implementação de ações políticas, sociais e econômicas para o desenvolvimento sustentável de uma bacia hidrográfica.…”
Section: Introductionunclassified
“…Em diversas regiões do Brasil foram realizados alguns trabalhos que identificaram distribuições teóricas que melhor se adequaram a determinadas séries históricas pluviométricas. Por exemplo, Assis (1993) avaliou o ajuste da função Gama em Pelotas-RS; Botelho e Morais (1999) e Morais et al (2001) avaliaram a distribuição Gama em Lavras -MG; Catalunha et al (2002) avaliaram cinco funções densidade de probabilidade a séries de precipitação em Minas Gerais; Neto et al (2005) aplicaram cinco funções densidade de probabilidade a séries pluviométricas em Piracicaba -SP; Sampaio et al (2007) avaliaram as distribuições decendiais no Estado do Paraná; Souza et al (2010) compararam as distribuições de probabilidade da precipitação mensal no Estado de Pernambuco; Oliveira et al (2010) avaliaram a precipitação provável para Alegre -ES através da distribuição de probabilidade Gama.…”
Section: Introductionunclassified